Carving of a gaja vyala (elephant with wings) - Temples of India Project Team (Jio Institute, 2024)
Relief carving of hybrid creatures like kinnaras, vyalas, and makara feature all around the adhisthana. Seen here is a carving of gaja vyala (elephant with wings).